Contribution of Cell Surface Hydrophobicity in the Resistance of Staphylococcus aureus against Antimicrobial Agents - Puja Lather; A. K. Mohanty; Pankaj Jha; Anita Kumari Garsa (Biochemistry Research International)
Staphylococcus aureus is found in a wide variety of habitats, including human skin, where many strains are commensals that may be clinically significant or contaminants of food. To determine the physiological characteristics of resistant strain of Staphylococcus aureus against pediocin, a class IIa bacteriocin, a resistant strain was compared with wild type in order to investigate the contribution of hydrophobicity to this resistance. Additional clumping of resistant strain relative to wild type in light microscopy was considered as an elementary evidence of resistance attainment. A delay in log phase attainment was observed in resistant strain compared to the wild type strain. A significant increase in cell surface hydrophobicity was detected for resistant strain in both hexadecane and xylene indicating the contribution of cell surface hydrophobicity as adaptive reaction against antimicrobial agents.